2017
DOI: 10.1007/s10565-017-9386-9
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the role of membrane microdomains during microbial infections

Abstract: Infectious diseases pose major socioeconomic and health-related threats to millions of people across the globe. Strategies to combat infectious diseases derive from our understanding of the complex interactions between the host and specific bacterial, viral, and fungal pathogens. Lipid rafts are membrane microdomains that play important role in life cycle of microbes. Interaction of microbial pathogens with host membrane rafts influences not only their initial colonization but also their spread and the inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 314 publications
(282 reference statements)
0
35
0
3
Order By: Relevance
“…Membrane rafts, which are highly dynamic membrane domains enriched in sphingolipids and cholesterol that mediate the compartmentalization of signaling proteins and receptors (Lingwood & Simons, 2010; Sezgin et al , 2017), have been shown to be utilized by numerous bacterial pathogens (reviewed in Refs: Lafont & van der Goot, 2005; Bagam et al , 2017). For example, Shigella uses its IpaB effector protein to bind the host raft‐associated CD44 transmembrane receptor (Lafont et al , 2002); entry of Listeria monocytogenes into host cells requires the localization of the host receptors E‐cadherin and HGF‐R/Met in specific lipid domains (Seveau et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane rafts, which are highly dynamic membrane domains enriched in sphingolipids and cholesterol that mediate the compartmentalization of signaling proteins and receptors (Lingwood & Simons, 2010; Sezgin et al , 2017), have been shown to be utilized by numerous bacterial pathogens (reviewed in Refs: Lafont & van der Goot, 2005; Bagam et al , 2017). For example, Shigella uses its IpaB effector protein to bind the host raft‐associated CD44 transmembrane receptor (Lafont et al , 2002); entry of Listeria monocytogenes into host cells requires the localization of the host receptors E‐cadherin and HGF‐R/Met in specific lipid domains (Seveau et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the diverse active mechanisms used by bacteria to mediate binding and invasion of host cells [e.g., pili, fimbriae, adhesins/invasins, T3SS (Pizarro-Cerda & Cossart, 2006;Stones & Krachler, 2016)], it has also become clear that efficient bacterial entry requires permissive sites in the host membrane. Membrane rafts, which are highly dynamic membrane domains enriched in sphingolipids and cholesterol that mediate the compartmentalization of signaling proteins and receptors (Lingwood & Simons, 2010;Sezgin et al, 2017), have been shown to be utilized by numerous bacterial pathogens (reviewed in Refs: Lafont & van der Goot, 2005;Bagam et al, 2017). For example, Shigella uses its IpaB effector protein to bind the host raft-associated CD44 transmembrane receptor (Lafont et al, 2002); entry of Listeria monocytogenes into host cells requires the localization of the host receptors E-cadherin and HGF-R/Met in specific lipid domains (Seveau et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, cholesterol and sphingolipid-rich detergent-insoluble membrane microdomains, commonly known as lipid rafts, could act as an interaction platform (Shaw 2006). A plethora of information suggests the harbouring and translocation of various signalling molecules to these microdomains and their subsequent interaction with lipid raft proteins (Caveolin-1/2 and Flotillin-1/2) (Anderson et al 1998; Bagam et al 2017; Barak and Muchova 2013; Bavari et al 2002; Lautz et al 2012). In this study, a significant induction in the expression of lipid raft proteins Caveolin-1/2 and Flotillin-1 following 6hCSE challenge in A549 cells was observed (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…They are found in diverse cell types and are especially abundant in the pulmonary endothelium [6,7]. Caveolae exert transporting and regulatory functions [8] and represent an important, intriguing target for drug delivery [912] in conditions including inflammation and tumors [13].…”
Section: Introductionmentioning
confidence: 99%